Evaluating The Effectiveness of Relaxation Techniques Combined with the K-Cat Exercises in Managing Urinary Incontinence in Female Population with Pelvic Floor Dysfunctions Through Primitive Reflex Integration - Sharma, Meenakshi; Goyal, Smita Barya; khan, Jafar; Annamalai, . KM.; Jain, Vardhman; Rai, Richa Hirendra; Jain, Preksha; Bedi, Parneet Kaur; khera, Neha; Joshi, Jayesh (Journal of Neonatal Surgery, 2025)
Urinary incontinence, defined as the involuntary loss of urine, is frequently associated with an overactive detrusor muscle. It commonly affects women, especially those over the age of 60, and is often triggered by activities such as coughing or sneezing. While neurological conditions and tumors can cause incontinence, it is most often linked to pelvic floor dysfunction, including excessive activity of the pelvic floor muscles. This study aims to examine the impact of traditional exercises on urinary incontinence along with K-CAT exercises, a modern technique that incorporates coordination between pelvic floor function, breathing, and jaw positioning.1 Objective Evaluating The Effectiveness of Relaxation Techniques Combined with Exercises in Managing Urinary Incontinence in Female Population with Pelvic Floor Dysfunctions Through Primitive Reflex Integration